Involvement of SIRT1-mediated aging in liver diseases - Zhang, Yueming; Gong, Chang; Tao, Lina; Zhai, Jinghui; Huang, Fengwei; Zhang, Sixi (Frontiers in Cell and Developmental Biology, 2025)
Liver disease is a significant global health issue, responsible for millions of deaths annually. Aging, characterized by the gradual decline in cellular and physiological functions, impairs tissue regeneration, increases susceptibility to liver diseases, and leads to a decline in liver health. Silent information regulator 1 (SIRT1), a NAD⁺-dependent deacetylase, has emerged as a pivotal factor in modulating age-related changes in the liver. SIRT1 preserves liver function by regulating essential aging-related pathways, including telomere maintenance, epigenetic modifications, cellular senescence, intercellular communication, inflammation, and mitochondrial function. Notably, SIRT1 levels naturally decline with age, contributing to liver disease progression and increased vulnerability to injury. This review summarizes the regulatory role of SIRT1 in aging and its impact on liver diseases such as liver fibrosis, alcoholic associated liver disease (ALD), metabolic dysfunction-associated steatotic liver disease (MASLD), and metabolic dysfunction-associated steatohepatitis (MASH), hepatocellular carcinoma (HCC). We also discuss emerging therapeutic approaches, including SIRT1 activators, gene therapy, and nutritional interventions, which are evaluated for their potential to restore SIRT1 function and mitigate liver disease progression. Finally, we highlight future research directions to optimize SIRT1-targeted therapies for clinical applications in age-related liver conditions.